Factors Affecting Farmers Decisions on Fertilizer Use: A Case Study for the Chaobai Watershed in Northern China - Zhou, Yuan; Yang, Hong (Consilience, 2010)
The Chaobai watershed in northern China is the most important source of drinking water for Beijing. The level of fertilizer use, especially overuse, as well as farming practices in the region have therefore a great impact on the water quality downstream. This study analyses the factors influencing farmers’ decision on fertilizer use and the implications for water quality. The analysis is based on a survey of 349 farm households. It takes into consideration both farm and farmer specific characteristics and farmers’ subjective evaluation of factors shaping their decisions. Regression models are used to examine the determinants of fertilizer use intensity across farm households and to investigate the factors influencing the overuse of nitrogen. The results suggest the significance of many of these ‘subjective’ factors, indicating the importance of considering them in the analyses. The results also show that irrigation, gains in crop yield and farming goal of earning are positively correlated to fertilizer use intensity while farm size, manure application, soil fertility and the distance to fertilizer market are negatively correlated. Investigation of the overuse problem shows that higher education level significantly reduces the probability of overfertilization. Based on these findings a few policy relevant implications are discussed.